2018
DOI: 10.1111/cas.13730
|View full text |Cite
|
Sign up to set email alerts
|

Clinical practice guidance for next‐generation sequencing in cancer diagnosis and treatment (Edition 1.0)

Abstract: In Japan, the social (medical) health‐care system is on the way to being developed to advance personalized medicine through the implementation of cancer genomic medicine, known as “cancer clinical sequencing,” which uses a next‐generation sequencer. However, no Japanese guidance for cancer genomic testing exists. Gene panel testing can be carried out to help determine patient treatment, confirm diagnosis, and evaluate prognostic predictions of patients with mainly solid cancers for whom no standard treatment i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 2 publications
1
48
0
Order By: Relevance
“…Evidence levels 1A‐3A in the Clinical Practice Guidelines for Next Generation Sequencing in Cancer Diagnosis and Treatment correspond to evidence levels A‐C in the guidelines published by the Association for Molecular Pathology, ACMG, American Society of Clinical Oncology, and College of American Pathologists . Therefore, the same percentage (ie, 59.4%) of cases was also judged as positive for aberrations based on evidence levels A‐C; ie, they had clinically significant gene aberrations.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…Evidence levels 1A‐3A in the Clinical Practice Guidelines for Next Generation Sequencing in Cancer Diagnosis and Treatment correspond to evidence levels A‐C in the guidelines published by the Association for Molecular Pathology, ACMG, American Society of Clinical Oncology, and College of American Pathologists . Therefore, the same percentage (ie, 59.4%) of cases was also judged as positive for aberrations based on evidence levels A‐C; ie, they had clinically significant gene aberrations.…”
Section: Resultsmentioning
confidence: 98%
“…Actionable gene aberrations for drug selection were those predicted to confer sensitivity/resistance to either an approved targeted agent or an experimental targeted agent currently in clinical trials. Evidence levels were added to each gene aberration according to Clinical Practice Guidance for Next Generation Sequencing in Cancer Diagnosis and Treatment (issued by the Japanese Society of Medical Oncology, Japan Society of Clinical Oncology, and the Japanese Cancer Association) . The guidance cites the following levels of evidence for each gene aberration: level 1A, a Pharmaceuticals and Medical Devices Agency (PMDA)‐approved biomarker for the tumor type; 1B, an FDA‐approved biomarker for the tumor type (not approved by the PMDA) or a biomarker verified by a prospective molecularly driven clinical trial; 2A, a biomarker identified by subgroup analysis in a prospective clinical trial; 2B, an approved biomarker for a different tumor type or a biomarker with evidence supporting its clinical utility; 3A, a biomarker with evidence of proof‐of‐concept in at least one case report; 3B, a biomarker with evidence obtained from in vitro/in vivo experiments; and 4, other gene mutations in cancer.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Liquid biopsy is a safe method for repeated collection of circulating tumor DNA (ctDNA) during the course of treatment, and ctDNA is more representative of tumor heterogeneity compared with tumor DNA collected from a single tumor site. Next‐generation sequencing (NGS) has also emerged over the last decade as an efficient approach to the detection of genetic alterations, having the advantage that it is able to detect many genetic mutations in parallel . Such an advantage is relevant to clinical practice, in which it is important to detect several different genomic mutations rapidly.…”
Section: Introductionmentioning
confidence: 99%